Representation, Exemplification, and Risk: Resonance of Tobacco Graphic Health Warnings Across Diverse Populations. Issue 8 (2nd August 2016) - Bigman, Cabral A.; Nagler, Rebekah H.; Viswanath, K.
ABSTRACT: As countries implement Article 11 of the World Health Organization (WHO) Framework Convention on Tobacco Control, graphic warning labels that use images of people and their body parts to illustrate the consequences of smoking are being added to cigarette packs. According to exemplification theory, these case examples—exemplars—can shape perceptions about risk and may resonate differently among demographic subpopulations. Drawing on data from eight focus groups ( N  = 63) with smokers and nonsmokers from vulnerable populations, this qualitative study explores whether people considered exemplars in their reactions to and evaluations of U.S. graphic health warning labels initially proposed by the Food and Drug Administration. Participants made reference to prior and concurrent mass media messages and exemplars during the focus groups and used demographic cues in making sense of the images on the warning labels. Participants were particularly sensitive to age of the exemplars and how it might affect label effectiveness and beliefs about smoking. Race and socioeconomic status also were salient for some participants. We recommend that exemplars and exemplification be considered when selecting and evaluating graphic health warnings for tobacco labels and associated media campaigns.